2017
DOI: 10.1080/09602011.2017.1377087
|View full text |Cite
|
Sign up to set email alerts
|

Effect of activity-based mirror therapy on lower limb motor-recovery and gait in stroke: A randomised controlled trial

Abstract: Activity-based MT facilitates motor recovery of the lower limb as well as reduces gait deviations among chronic poststroke hemiparetic subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 57 publications
1
39
0
3
Order By: Relevance
“…Improvements which are seen in gait and function due to mirror therapy are supported by Arya et al, who demonstrated that activity-based mirror therapy accelerates lower limb motor recovery and reduces gait deviations amongst chronic poststroke subjects [7] .…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Improvements which are seen in gait and function due to mirror therapy are supported by Arya et al, who demonstrated that activity-based mirror therapy accelerates lower limb motor recovery and reduces gait deviations amongst chronic poststroke subjects [7] .…”
Section: Discussionmentioning
confidence: 89%
“…Mirror therapy has proved to be effective for the recovery of the upper limb after stroke. Studies regarding the effectiveness of mirror therapy on lower limb recovery after stroke are few [7] .…”
Section: Introductionmentioning
confidence: 99%
“…After reviewing the full papers to obtain additional details and excluding studies for various reasons (no relevant outcomes reported, an irrelevant study design, non-randomized studies and publications in languages other than English and Chinese), 13 studies including 572 patients fulfilled the inclusion criteria and were included in the final analysis. 23–35…”
Section: Resultsmentioning
confidence: 99%
“…23 As for assessment of balance, the Brunnel Balance Assessment, 35 the Berg Balance Scale 27,29,34 and quantitative evaluations of balance 28,33 were used in five studies. Seven studies assessed lower extremity motor recovery, and four of them used the lower limb subscale of the Fugl-Meyer Assessment, [32][33][34][35] while the other three used Brunnstrom stages. 23,26,30 Three studies measured the spasticity of the ankle muscle using the Modified Ashworth Scale, 23,26,30 and passive range of motion of ankle dorsiflexion was reported in two studies.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…[15] The recovery grading then uses a 7 point hierarchy scale, in which stage 1 appears after stroke onset, that is flaccid stage, stage 2 up to 4 shows the development of spasticity synergy, stage 5 is where voluntary movement starts to dominate the synergy, and finally stage 6 shows how spasticity is no longer present, coordination and voluntary movements are near normal. [17,18] In the original published definition, the stage 7 of Brunnstrom's stage shows the presence of age appropriate normal variety of complex movement patterns, and there is no evidence of functional impairment when compared to the non-paretic limb. [19] This assessment could be done by physician's physical examination, evaluating both spasticity and synergy in both hemiplegic extremities, and its validity has also been published previously.…”
Section: Introductionmentioning
confidence: 99%